The Eloquent Mysteries, Rhetorical Finalities of Imperative in the Noble Quran, and Response to the Violators: Pragmatics - Jouani, Moulay Mehdi (Al-Ḍād Journal, 2022)
A meticulous rhetorical article in a detailed scientific response to the non-scientific doctrine that denies the Sunnah of the prophet (PBUH) and attempts to nullify the cornerstone and the hypothesis of Fasting, from a rhetorical and intentional perspective of the occurrence of the matter in the holy Qur'an. My method in response was influenced by the approach of the Egyptian critic Dr. Mustafa Nassef in his book "A Second Reading of Our Old Poetry", where he made the structure of Arabic poetry a complex subject that requires a thorough analytical reading, in a medical sense, in order to dive into the body of the studied material and extracts its deep secrets and psychological facts instead of the superficial anatomical reading influenced by the Impressionism, which in his view and ours is an outdated reading. As for the goal of the research, it is to fathom out the secrets of the subject's rhetoric in the Great Quran, by defending its miraculous language from the insults of the ignorants and the appeals of haters who are unaware of its purposes. He concluded that it is necessary to confront the misconceptions of the invalidators with a sober scientific approach and a sound critical lesson. Keywords: eloquence, pragmatics, imperative in the Quran, criticism